The effect of information, education and communication on knowledge and practice regarding prevention/treatment of iron deficiency anaemia among the antenatal women attending primary health centre in Puducherry, India: a randomised control study - Chandran, Athul; M., Subashini; Kate, Nina (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2019)
Background: IEC (Information, Education, and Communication) strategies may help pregnant women to prevent disease and to improve and maintain health. The present study was carried out with an aim to evaluate the effectiveness of IEC in improving the knowledge and practice regarding prevention/treatment of iron deficiency anaemia among the antenatal women attending Primary Health Centre in Puducherry. Methods: The present study was carried out in Puducherry, as a randomised control trial among antenatal mothers attending antenatal clinics in Primary Health Centre from February 2016 to August 2017. Block randomization technique was used to designate study participants into intervention and non-intervention groups. The minimum required sample size was calculated to be 84 in each group. Then intervention (Information, Education and Communication) was given to these antenatal women by using interpersonal communication methods, PowerPoint presentation and audio visual aids. Results: Correct responses to the questions were compared among the intervention and non intervention group in pre test and post test. It was noted that the proportion of correct responses were significantly higher among intervention group than that of non-intervention groups. Conclusions: Well planned and tailor made IEC material, acceptable by the regional population, by using various modes of interpersonal communication, improves the knowledge and practice of the antenatal mothers. It was also found that the haemoglobin levels of mothers in the intervention group were higher than the antenatal mothers who did not receive any IEC intervention.